Association Between Sense of Coherence and Health Outcomes at 10 and 20 Years Follow-Up: A Population-Based Longitudinal Study in Germany - Dziuba, Anna; Krell-Roesch, Janina; Schmidt, Steffen C. E.; Bös, Klaus; Woll, Alexander (Frontiers in Public Health, 2021)
Background: The sense of coherence (SOC) is reported to influence health, but health may also have an impact on SOC. The objective of this study was to examine the longitudinal associations between SOC and selected self-reported and physician-assessed health outcomes over a period of 10 and 20 years and to determine the predominant direction of the associations. Methods: We conducted a population-based, longitudinal study, involving 392 participants (188 females and 204 males; mean age 43.01 years) who were followed for a median of 10 and 18 years. Analyses of variance were carried out to examine the longitudinal associations between SOC at baseline and health outcomes (i.e., self-rated health status, SHS; physical health status assessed by a physician, PHS; self-reported satisfaction with life, SWL) at follow-ups. The direction of associations was examined using a cross-lagged model on correlation coefficients. Results: There were significant group effects for SOC at baseline on SHS at 20-year follow-up (F = 4.09, p = .018, ηp² = .041), as well as on SWL at 10-year (F = 12.67, p < .01, ηp² = .072) and at 20-year follow-up (F = 8.09, p < 0.1, ηp² = .069). SHS (r = .238, p < .01), PHS (r = -.140, p < .05) and SWL (r = .400, p < .01) predicted SOC at 10-year follow-up stronger than vice versa. The direction of associations between SOC and health parameters at 20-year follow-up was less consistent. Conclusions: The long-term associations between SOC and self-reported and physician-assessed health may be reciprocal in community-dwelling adults. More research is needed to examine the predictive power of health on SOC and whether interventions targeted at improving health parameters, may impact SOC.